Acquired phototrophy through retention of functional chloroplasts increases growth efficiency of the sea slug Elysia viridis. - Finn A Baumgartner; Henrik Pavia; Gunilla B Toth (PLoS ONE, 2015)
Photosynthesis is a fundamental process sustaining heterotrophic organisms at all trophic levels. Some mixotrophs can retain functional chloroplasts from food (kleptoplasty), and it is hypothesized that carbon acquired through kleptoplasty may enhance trophic energy transfer through increased host growth efficiency. Sacoglossan sea slugs are the only known metazoans capable of kleptoplasty, but the relative fitness contributions of heterotrophy through grazing, and phototrophy via kleptoplasts, are not well understood. Fitness benefits (i.e. increased survival or growth) of kleptoplasty in sacoglossans are commonly studied in ecologically unrealistic conditions under extended periods of complete darkness and/or starvation. We compared the growth efficiency of the sacoglossan Elysia viridis with access to algal diets providing kleptoplasts of differing functionality under ecologically relevant light conditions. Individuals fed Codium fragile, which provide highly functional kleptoplasts, nearly doubled their growth efficiency under high compared to low light. In contrast, individuals fed Cladophora rupestris, which provided kleptoplasts of limited functionality, showed no difference in growth efficiency between light treatments. Slugs feeding on Codium, but not on Cladophora, showed higher relative electron transport rates (rETR) in high compared to low light. Furthermore, there were no differences in the consumption rates of the slugs between different light treatments, and only small differences in nutritional traits of algal diets, indicating that the increased growth efficiency of E. viridis feeding on Codium was due to retention of functional kleptoplasts. Our results show that functional kleptoplasts from Codium can provide sacoglossan sea slugs with fitness advantages through photosynthesis.